Complement 3 Receptor Expression in Individuals with Type 2 Diabetes - Ly, Judy; Morris, Devin; Lagman, Minette; Ng, Christopher; Anderson, Shelby; Daliva, John; Muwanas, Naji; Tarash, Igal; Ochoa, Cesar; Sathananthan, Airani; Venketaraman, Vishwanath (Recent Patents on Anti-Infective Drug Discovery, 2016)
Background: According to the World Health Organization, as of 2014 9% of the world’s adult population is affected by diabetes. Uncontrolled diabetes is a pro-inflammatory process that increases generation of reactive oxygen species (ROS). Methods: The production of ROS leads to a chronic increase in oxidative stress which results in an increased susceptibility to infections. Individuals with type 2 diabetes mellitus (T2DM) are highly susceptible to Mycobacterium tuberculosis (M. tb) infection. Previous research has demonstrated that glutathione (GSH) plays an important role in the control of M. tb infection. Recent studies have demonstrated that phagocytosis of M.tb is diminished in patients with T2DM. Phagocytosis in macrophages is thought to be mediated in part by complement protein 3b (C3b)-complement protein receptor 3b (C3R) interactions. Since C3b production is not diminished in patients with T2DM we propose that C3R production is reduced and is the cause for impaired macrophage phagocytosis as well as IL-12 and IFN-γsignaling. Conclusion: This study utilizes a quantitative PCR (qPCR), demonstrating decreased transcription of C3R mRNA in patients with T2DM as compared to non-diabetics.
Keywords: complement receptors